In vitro investigation of King Oyster Mushroom [Pleurotus eryngii (DC.: Fr.) Quel.] strains in vegetative growing phases - Szarvas, J.; Naár, Z.; Geösel, A.; Győrfi, J. (International Journal of Horticultural Science, 2010)
The king oyster mushroom ( Pleurotus eryngii) is more and more popular amongst the producers due to its excellent taste and relatively easy cultivation . In the course of our work we collected 15 king oyster mushroom strains from various habitats in Hungary in order to get a better picture about the growth of the vegetative mycelia of the species and its different strains. In the in vitro experiments we investigated the growth of the strains at various temperatures and pH. incubated them in light and darkness and in aerobic and anaerobic atmosphere. In addition to these we measured the weight of dry mycelia produced in a given time by the strains. Our results showed that the above mentioned environmental conditions resulted in a very different growth rate of the vegetative mycelia of the various P. eryngii strains. These results may provide valuable data about the vegetative phase of the cultivation.